2009
DOI: 10.1139/h08-143
|View full text |Cite
|
Sign up to set email alerts
|

Canada’s physical activity guide recommendations are a low benchmark for Manitoba adults

Abstract: Canada's Physical Activity Guide to Healthy Active Living (CPAG) is the national reference for messaging on physical activity for health benefits, yet few studies have examined population activity levels in relation to its recommendations. As part of the province-wide in motion initiative, we obtained a baseline measurement of the physical activity levels of adult Manitobans. Physical activity levels were benchmarked against CPAG recommendations and were compared with criteria used in previous surveys. A strat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
6
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 25 publications
(55 reference statements)
5
6
1
Order By: Relevance
“…Thus, it appears that the overall mean physical activity level is skewed by a few select individuals who do a lot of activity. Interesting to note however, is that 64% of individuals met the CPAG guidelines with at least light activity, which is similar to other self-report studies which also included both occupational and leisure time physical activity in their analysis (Ready et al, 2009). Had we used the new physical activity recommendations for Canadians (CSEP and Participaction, 2010) which do not include light activity, we would have seen a much smaller proportion of people meeting the guidelines.…”
Section: Patient Characteristicssupporting
confidence: 77%
See 3 more Smart Citations
“…Thus, it appears that the overall mean physical activity level is skewed by a few select individuals who do a lot of activity. Interesting to note however, is that 64% of individuals met the CPAG guidelines with at least light activity, which is similar to other self-report studies which also included both occupational and leisure time physical activity in their analysis (Ready et al, 2009). Had we used the new physical activity recommendations for Canadians (CSEP and Participaction, 2010) which do not include light activity, we would have seen a much smaller proportion of people meeting the guidelines.…”
Section: Patient Characteristicssupporting
confidence: 77%
“…While the current study found that the majority of people met the guidelines through light activity, Ready et al, (2009) found that the main way to meet the CPAG guidelines was through moderate activity, which perhaps suggests a difference in activity choices between those with type 2 diabetes and those without. While recent research has shown that health benefits are the same for low to moderate exercise as compared to moderate to vigorous exercise when matched for energy expenditure (Hansen et al, 2009), other research reports greater health benefits from more intense exercise.…”
Section: Patient Characteristicscontrasting
confidence: 65%
See 2 more Smart Citations
“…A wealth of evidence clearly demonstrates the benefits of participating in PA [1], [4], [27], [28], however despite this research, the majority of Canadians are still physically inactive [5], [6]. In a recent publication with accelerometer data from Canada’s Health Measures Survey, only 15% of Canadians are participating in 150 minutes of moderate to vigorous PA per week in 10 minute bouts and only 53% of Canadians participate in 30 minutes of moderate to vigorous PA at least one day per week [6], meaning that the majority of Canadians are not active enough for minimum health benefits.…”
Section: Discussionmentioning
confidence: 99%